Reliability and usefulness of linear sprint testing in adolescent rugby union and league players - Darrall-Jones, J. D.; Jones, B.; Roe, G.; Till, K. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to evaluate (a) whether there were differences in sprint times at 5, 10, 20, 30, and 40 m between rugby union and rugby league players, (b) determine the reliability and usefulness of linear sprint testing in adolescent rugby players. Data were collected on 28 rugby union and league academy players over 2 testing sessions, with 3-day rest between sessions. Rugby league players were faster at 5 m than rugby union players, with further difference unclear. Sprint time at 10, 20, 30, and 40 m was all reliable (coefficient of variation [CV] = 3.1, 1.8, 2.0, and 1.3%) but greater than the smallest worthwhile change (SWC [0.2 × between-subject SD]), rating the test as marginal for usefulness. Although the test was incapable of detecting the SWC, we recommend that practitioners and researchers use Hopkins' proposed method; whereby plotting the change score of the individual at each split (±typical error [TE] expressed as a CV) against the SWC and visually inspecting whether the TE crosses into the SWC are capable of identifying whether a change is both real (greater than the noise of the test, i.e., >TE) and of practical significance (>SWC). Researchers and practitioners can use the TE and SWC from this study to assess changes in performance of adolescent rugby players when using single beam timing gates.